Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai di Dinas Komunikasi dan Informatika Kabupaten Rembang - Rojikin, Mohammad; Nurhidayati, Anik (Universitas Pahlawan Tuanku Tambusai, 2025)
Worker motivation and the quality of their work environment are the focus of this study on the influence of the Rembang Regency Communication and Informatics Office on productivity. The participants in this study were people who work at the Rembang Regency Communication and Informatics Office. We used saturated probability sampling for our sampling. The sample size for this study was 62 people. The data were analyzed using multiple linear regression. The results showed that although work environment variables did not have a significant impact on employee performance, motivation had a significant impact. The Adjusted R Square value of this study was 0.347, or 34.7%, which indicates that the variability of the dependent variable—the independent variable that includes motivation and work environment—was 34.7% responsible for employee performance. Other independent variables, which were not explained in this study, reached 65.3% of the total..